(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
There are different ways to learn foreign languages. One of the effective methods is to read books in the original. These students’ reading skills and vocabulary also serves to increase wealth. In addition, he is learning the language gives more information about the culture and customs of the country. This in the article we discuss the positive influence of culture and lifestyle on learning foreign languages We will try to provide information about it. The article is in English and Uzbek Some of the polite words that exist are highlighted, of which there are two languages compared the similarities and differences.